The Students’ Errors In Using Simple Present Tense In Writing Descriptive Texts At SMK N 4 Padang - Dewi Murni; Lely Refnita (Universitas Pahlawan Tuanku Tambusai, 2023)
This study set out to identify the common errors made by students at SMKN 4 Padang when using the simple present tense to write descriptive texts. This study used a descriptive research design. The first graders at SMKN 4 Padang made up the study's population. In this study, a proportional stratified random sampling with a sample size of 31 students was used. Writing tests were used as the instrument for gathering data for this study. Using the Pearson Product Moment formula, the researcher examined the writing test's reliability. The test's correlation coefficient of 0.90 confirmed it. The analysis's findings demonstrated the validity of the writing test. It indicates that the test was valid. The findings of this study demonstrated that the first graders at SMKN 4 Padang made errors when using the simple present tense to write descriptive texts. It was established that 16% of students made a singular-plural error, 32% made a verb tense error, 38% made a spelling error, 90% made a punctuation error, and 96% made a capitalization error. Finally, it can be inferred from the results that the students at SMKN 4 Padang made a lot of errors on writing mechanics. It is advised that the teachers remind the students about grammatical errors, particularly in punctuation and capitalization, and help them develop their writing skills with active, creative, inventive, and enjoyable learning approaches. Grammar errors should be avoided when writing descriptive texts and students should practice more. It is also advised that future researchers use this research finding as a reference.